Analisis Semantik dan Tafsir Ayat-Ayat tentang Kesabaran (Ṣabr) dalam Al-Qur’an dan Implikasinya bagi Pengembangan Karakter Kesabaran dalam Pendidikan Islam - Titim Fatimah (CV. Kalimasada Group, 2025)
This study aims to analyze the meaning of ṣabr in the Qur’an through a semantic approach and exegetical studies, as well as to identify its implications for the development of patience as a character trait in Islamic education. The research method employed is library research with qualitative analysis, utilizing classical and contemporary tafsir sources such as Tafsir al-Ṭabarī, Tafsir al-Qurṭubī, and Tafsir al-Mishbāḥ. Semantic analysis of the root ṣ-b-r and its derivations across various verses reveals that ṣabr encompasses steadfastness, self-control, perseverance in trials, and consistency in righteousness. The findings show that ṣabr in the Qur’an has three main dimensions: patience in obedience, patience in avoiding sins, and patience in facing hardships. The implications for Islamic education include integrating patience values into the curriculum, habituating patient behavior through teacher role models, and fostering character through experiential learning. This study emphasizes that developing patience should not only be cognitive but must also address the affective and psychomotor aspects of learners.